Complete Osseointegration of a Retrieved 3-D Printed Porous Titanium Cervical Cage - van den Brink, Wimar; Lamerigts, Nancy (Frontiers in Surgery, 2020)
Introduction: Porous 3D-printed titanium has only recently been introduced for spinal applications. Evidence around its use is currently limited to animal studies and only few human case series. This study describes the histological findings of a retrieved EIT cervical cage, explanted 2 years after insertion. Materials and Methods: The patient underwent a double level C4/C5 & C5/C6 anterior cervical decompression using EIT cervical cages without an anterior plate. Two years later the C6/7 level degenerated and began to cause myelopathic symptoms. In order to address the kyphotic imbalance of the cervical spine and fix the C6/7 level, the surgeon decided to remove the C5/6 cervical cage and bridge the fusion from C4 to C7 inclusive. The retrieved cage was histologically evaluated for bone ingrowth and signs of inflammation. Results: MRI demonstrated spinal canal stenosis at C6/C7. Plain radiographs confirmed well-integrated cervical cages at 2 years postoperative. The peroperative surgical need to use a chisel to remove the implant at C5/C6 reconfirmed the solid fusion of the segment. Macroscopically white tissue, indicative of bone, was present at both superior and inferior surfaces of the explanted specimen. Histological evaluation revealed complete osseointegration of the 5 mm high EIT Cellular Titanium® cervical cage, displaying mature lamellar bone in combination with bone marrow throughout the cage. Furthermore, a pattern of trabecular bone apposition (without fibrous tissue interface) and physiological remodeling activity was observed directly on the cellular titanium scaffold. Conclusion: This histological retrieval study of a radiologically fused cervical EIT cage clearly demonstrates complete osseointegration within a 2-year time frame. The scaffold exhibits a bone in growth pattern and maturation of bone tissue similar of what has been demonstrated in animal studies evaluating similar porous titanium implants. The complete osseointegration throughout the cage indicates physiological loading conditions even in the central part of the cage. This pattern suggests the absence, or at least the minimization, of stress-shielding in this type of porous titanium cage.